2015
DOI: 10.35680/2372-0247.1055
|View full text |Cite
|
Sign up to set email alerts
|

The patient portal and abnormal test results: An exploratory study of patient experiences

Abstract: Many health care institutions are implementing patient portals that allow patients to track and maintain their personal health information, mostly in response to the Health Information Technology for Economic and Clinical Health Act requirements. Test results review is an area of high interest to patients and provides an opportunity to foster their involvement in preventing abnormal test results from being overlooked, a common patient safety concern. However, little is known about how patients engage with port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 14 publications
1
60
0
Order By: Relevance
“…Patients want more than an in-depth explanation of the purpose of laboratory tests, the result, and reference range. Rather, our findings suggest that what matters to patients is what the results mean, in simple language, including how they fit in the patient’s overall medical history and the next steps to take with their care 1,12,13,19,20. Additionally, patients reported that physicians skip high-touch follow-up of laboratory reports.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Patients want more than an in-depth explanation of the purpose of laboratory tests, the result, and reference range. Rather, our findings suggest that what matters to patients is what the results mean, in simple language, including how they fit in the patient’s overall medical history and the next steps to take with their care 1,12,13,19,20. Additionally, patients reported that physicians skip high-touch follow-up of laboratory reports.…”
Section: Discussionmentioning
confidence: 84%
“…Patients want immediate access to their medical reports, whether results are normal or not, and find information written in lay language to be helpful 812. Direct access to medical records enhances patient empowerment and involvement in medical care, which is associated with better outcomes,13,14 better adherence to treatment recommendations, and greater satisfaction with the health care system 15,16.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no mechanism to measure these important outcomes at a system-wide level. 14 Capturing information about PCC in this manner could facilitate assessment and tracking of these crucial aspects of health care quality within and across VHA facilities.…”
Section: The Importance Of Patient-centered Communication In the Vhamentioning
confidence: 99%
“…Christensen showed that patients are very satisfied with receiving their laboratory results through a portal. Similarly, results of a study conducted by Giardina showed that patients prefer to receive their abnormal laboratory results through a portal. However, results of some other studies revealed that providing patients with online laboratory results can raise their concerns regarding information confidentiality .…”
Section: Introductionmentioning
confidence: 96%
“…However, results of some other studies revealed that providing patients with online laboratory results can raise their concerns regarding information confidentiality . Besides, problems related to health and computer literacy were other concerns related to online communication of laboratory results . Some other concerns are negative emotional reaction of patients when they receive their abnormal laboratory results and inability to understand normal and abnormal results that require a physician to explain the results …”
Section: Introductionmentioning
confidence: 99%